2014
DOI: 10.3390/polym6030667
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of RC Members Using Externally Bonded Aluminum-Glass Fiber Composite Beams

Abstract: This study concerns improvement of flexural stiffness/strength of concrete members reinforced with externally bonded, aluminum-glass fiber composite (AGC) beams. An experimental program, consisting of seven reinforced concrete slabs and seven reinforced concrete beams strengthened in flexure with AGC beams, was initiated under four-point bending in order to evaluate three parameters: the cross-sectional shape of the AGC beam, the glass fiber fabric array, and the installation of fasteners. The load-deflection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…γ 3 is the ratio between yield strength to the ultimate tensile strength of the reinforcement, which may have different values corresponding to the commonly used reinforcements in RC elements [1], as shown in Table 2. S c is the section modulus for the edge fibre of the section where the tensile stress of the section is caused by external loads [34,35], which is shown in Equation ( 13) for a rectangular section. f r is the rupture modulus of concrete, which may be expressed in Equation ( 14) in ksi units for normal weight concrete [1].…”
Section: Strength Limit Statementioning
confidence: 99%
See 1 more Smart Citation
“…γ 3 is the ratio between yield strength to the ultimate tensile strength of the reinforcement, which may have different values corresponding to the commonly used reinforcements in RC elements [1], as shown in Table 2. S c is the section modulus for the edge fibre of the section where the tensile stress of the section is caused by external loads [34,35], which is shown in Equation ( 13) for a rectangular section. f r is the rupture modulus of concrete, which may be expressed in Equation ( 14) in ksi units for normal weight concrete [1].…”
Section: Strength Limit Statementioning
confidence: 99%
“…Based on elastic principles and the features of the gross concrete section, the tensile stress f b in the bottom fibres caused by M uf for a rectangular RC section can be calculated using Equation (35):…”
Section: Fatigue Limit Statementioning
confidence: 99%
“…FRP telah diterapkan pada beberapa struktur sebagai perkuatan untuk beton pada struktur baru atau struktur yang telah lama (Hamid & Hutchinson, 2001). Penggunaan FRP sebagai perkuatan eksternal pada balok beton bertulang meningkatkan beban retak awal, beban leleh, dan puncak (Hong et al, 2014). Perkuatan balok beton bertulang dengan pemasangan GFRP tipe lembaran pada bagian bawah balok dapat meningkatkan kapasitas lentur balok dibandingkan dengan balok kontrol atau tanpa perkuatan (Meikandaan & Murthy, 2017).…”
Section: Pendahuluanunclassified
“…According to the review by Panigrahi et al (2014), this method was using for the strengthening and repair of structures due to actions of ageing, poor maintenance, corrosion of steel reinforcement, defects in construction, exposure to harmful environments and damage in case of seismic events, and the deficiency of the initial design such as demand in the serviceability state, the durability and ductility of reinforced concrete structures. Most studies indicated that the use of the EB technique would enhance the load carrying, shearing and flexural capacities of RC members (Dai et al 2005, Panigrahi et al 2014, Ali et al 2014, Hong et al 2014. At the present, the study of the EB strengthening method for the RC members is extending to consider the various and combined effects of elevated temperature and environment conditions, the interfacial behavior and the new approach of numerical analysis (Dai 2005, Burke et al 2013, Domenico et al 2015, and Firmo et al 2015.…”
Section: Assessments Of the Current Strengthening Methodsmentioning
confidence: 99%